Acetic acid effects on methanogens in the second stage of a two-stage anaerobic system - Xiao, Keke (2016)
This study reports on biomass tolerance towards high concentrations of acetic acid (HAc) within the system. Biomass from the second stage of a two-stage anaerobic sludge digestion system was used for this study. Microbial community analysis by 454 pyrosequencing highlighted hydrogenotrophic Methanomicrobiales was the predominant archaeal population in the second stage (>99% of the total archaeal community). Second stage biomass degraded HAc up to 4200 mg HAc L-1 without observable lag phase. However, at HAc-shock loading of 7400 mg HAc L-1, it showed a one day lag phase associated with decreased biomass activity. After stepwise HAc-acclimation over 27 d, the biomass degraded HAc of up to 8200 mg HAc L-1 without observable lag phase. The dominance of Methanomicrobiales had remained unchanged in proportion - while the total archaeal population increased during acclimation. This study showed stepwise acclimation could be an approach to accommodate HAc accumulation and hence higher concentrations resulting from an enhanced first stage. Keywords: Acclimation; Acetic acid inhibition; Biomass activity; Hydrogenotrophic methanogens; Pyrosequencing; Two-stage anaerobic system